\(\left|2x-1\right|=x\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-1=x\\2x-1=-x\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{1}{3}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x-1=x\\2x-1=-x\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x-1=0\\3x-1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{1}{3}\end{matrix}\right.\)
Giải : \(|2x-1|=x \Leftrightarrow \begin{cases} 2x-1=x\\ 2x-1=-x \end{cases} \begin{cases} x=1\\ x=\dfrac{1}{3} \end{cases} \)
vì \(\left|2x-1\right|\) \(\ge\) 0
=> x \(\ge\) 0
+) 2x -1 = x
<=> 2x -x = 1
=> x = 1 (t/m)
+) 2x -1 = -x
<=> 2x +x = 1
<=> 3x =1
=> x = 1/3 ( t/m )